Teachers’ Perspectives on the Use of Rhymes in Teaching English as a Second Language at Early Childhood Development Level in Gweru Rural District Primary Schools of Zimbabwe - Emely Muguwe; Nomatter Manzunzu; Angela Mutonganavo (Center for Research Implications and Practice (CRIP), 2023)
The paper explored teachers perspectives on the use of rhymes in the teaching of English as a second language at ECD level in Gweru rural district primary schools. A mixed methods approach in the form of a descriptive survey was used in this study. Ten school heads and fifty (50) Early Childhood Development teachers were purposively selected. These responded to interviews and questionnaires respectively. The findings revealed that when teaching English, teachers concentrated more on teaching language structures more than allowing learners to learn through action rhymes. While participants agreed that learners benefit tremendously from reciting action rhymes which in turn promote logical thinking it was also noted that teachers tended to use the same rhymes over and over again without really concentrating on form and structure. This has been attributed to lack of resources such as books and technological equipment. Participants felt that not much was being during training on the use of rhymes in teaching English as a second language. Teachers lacked skills on use of rhymes and of producing original rhymes. The implications are that teachers need training on the use of rhymes in teaching English as second language. The recommendations are that rhymes should underpin the teaching of English as a second language in order to stimulate learner’s abilities through action. Teachers should keep abreast with new and meaningful rhymes.